Formulasi Strategi Pengembangan Bisnis Berbasis Analisis SWOT dan Orientasi Pasar: Studi pada Produk Korean Pancake di Indonesia - Mohammad Afrizal miradji; Bayu Adi; Putri Ayu; Chika Aulia; Nabila Natcjwa; Ayunda Frischa (Journal of Economics, Management, and Accounting, 2025)
The phenomenon of the Korean Wave (Hallyu) has influenced lifestyle and consumption trends among Indonesian society, including in the culinary sector. This study aims to analyze market potential and formulate business development strategies for Korean Pancakes (Hotteok) in Indonesia. The research method used is qualitative descriptive with a case study approach, through observation of digital sales trends, interviews with business actors and consumers, as well as literature analysis. The results show that Korean Pancakes have high market potential among young consumers, mainly due to the support of Korean cultural trends and increased food consumption through online platforms. SWOT analysis reveals that the main strengths are product uniqueness and visual appeal that aligns with social media trends, while weaknesses include production limitations and product shelf life. Significant opportunities lie in digital collaboration and online market expansion, with the main threats being modern dessert competition and rapid trend changes. Recommended development strategies include flavor variant innovation, brand strengthening through social media, digital distribution optimization, and the development of long-lasting products. Overall, this study confirms that the success of the Korean Pancake business in Indonesia depends on continuous innovation, market trend adaptation, and the establishment of a strong brand identity.